2021
DOI: 10.2399/ana.21.829636
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of sildenafil citrate in isoniazid-rifampicin induced histomorphological changes in liver of albino mice

Abstract: Objectives: The objective of the study was to reveal the reversal of histo-morphological changes in mice liver induced by combined isoniazid-rifampicin (INH-RIF) therapy with sildenafil treatment. Methods: Twenty-one mice weighing between 25–35 g were enrolled in the study. Randomisation was carried out by simple balloting method. The selected mice were sorted into three groups with 7 mice, each group. In group C (n=7) control group, mice were administered 0.4ml of saline per kg body weight daily intra periton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Hameed and Farooq [26] also found significant improvement in histological parameters of the liver in mice treated with SC for 21 days.…”
Section: Resultsmentioning
confidence: 81%
“…Hameed and Farooq [26] also found significant improvement in histological parameters of the liver in mice treated with SC for 21 days.…”
Section: Resultsmentioning
confidence: 81%
“…The results are in agreement with the works of Ibama et al [30], in which the administration of sildenafil and revive capsules were seen not to be hepatotoxic. Sildenafil citrate has been reported to reverse biochemical/histopathological changes in the liver due to jaundice and offer hepatoprotective action against drug-induced hepatotoxicity [31,32]. Some other studies have however reported hepatotoxic effects of increasing doses of sildenafil and the combination of sildenafil and tramadol in experimental models [1,33].…”
Section: Resultsmentioning
confidence: 99%